Cancer Care in Pandemic Times: Building Inclusive Local Health Security in Africa and India - Banda, Geoffrey; Mackintosh, Maureen; Njeru, Mercy Karimi; Makene, Fortunata Songora; Srinivas, Smita (International Political Economy Series, 2024)
This open access edited volume focuses on the scope and benefits of strengthening local industrial-health linkages. The Covid-19 pandemic collapsed international supply chains for health. That experience brought home to African policy makers the critical nature of local manufacturing capabilities for sustaining and strengthening health care, and highlighted the pandemic benefits of India's much stronger industrial base. At that time, a network of researchers in East Africa, India and the UK were investigating how to address the crisis of cancer care in low-resource health systems. Their project, uniquely, focused on the scope and benefits of strengthening local industrial-health linkages. The project researchers were also drawn into the pressing demands of Covid19 response. The result is this very timely book. The authors link their research on cancer to pandemic experience, and they draw sharp lessons for how countries can enhance their populations' health security. The authors argue that improving cancer care is crucial for human wellbeing and more inclusive health care. They challenge policy makers to bring together health needs, health innovations and improved industrial capabilities to embed better cancer care and broader health system improvement in local industrial innovation and development.